Gender differences in technical-tactical behaviour of La Liga Spanish football teams - Casal, C. A.; Losada, J. L.; Maneiro, R.; Ardá, A. (Journal of Human Sport & Exercise, 2021)
The aim of this study was to identify differences in technical-tactical behaviour between the men and women first division football teams of the Spanish league, to this end 68 matches corresponding to 2016/17 season were analysed. A comparative analysis of the medians was carried out using the Mann-Whitney U-tests were conducted as post hoc tests. The size effect of this test was calculated and, finally, we performed a grouping of the variables through the clustering bootstrapping technique in both groups. We have detected statistically significant differences (p < .01) regarding all accurate passes, in favour of men, as well as a greater number of yellow cards. In female football, a greater number of picking up free balls, interceptions, lost balls, recoveries and challenges are produced. Finally, in women's football a greater number of attacks are also carried out, both positional and counterattacks than in men. The clustering analysis allowed us to identify that in male football, the circumstance of receiving a red card is closely related to the number of goals conceded and most of the shots on goal are achieved by positional attacks. In the case of women's football, ball possession on own half is closely related to the number of losses. Data proves the existence of technical-tactical differences between male and female football of the La Liga teams. Such detailed analysis could be useful for gender-specific training information for optimal preparation. However, more research is warranted to establish the main gender differences and characterize women's football.